Evidence-Based Pharmaceutical Care in Community Pharmacies: A Survey of 595 French Pharmacists - Louis Bosson; Francesca Veyer; Jean-Didier Bardet; Céline Vermorel; Alison Foote; Benoit Allenet; Jean-Luc Bosson (MDPI AG, 2023)
We assessed the use of evidence-based practice (EBP) among pharmacists working in community pharmacies in France and the factors linked to this practice. During 3 months in 2018, an online survey was sent to over 7000 active pharmacists and posted on pharmacists' social media sites. In total, 595 pharmacists completed the questionnaire. The responders were on average younger than the general population of community pharmacists. The 40-item questionnaire described four fictional clinical cases reflecting typical situations (conventional medicine and complementary and alternative medicine) encountered daily by community pharmacists. Multiple-choice responses were proposed and scored according to whether they reflected EBP. A high total score indicated behaviour in line with EBP. We observed 344/595 participants with a positive EBP score (57.8% [53.7-61.8%]). Univariate and multivariate analyses were used to evaluate factors that might explain adherence to EPB (the pharmacy's characteristics, the pharmacist's status, the mode of continuing education and sources of information). The majority relied on pharmaceutical industry and other biased and/or non-evidence-based sources, particularly concerning information on homeopathic products. The consultation of independent reviews, health agency recommendations and peer-reviewed scientific journals was associated with evidence-based decisions. In contrast, reliance on pharmaceutical industry documents, personal experience and informal handbooks was linked to lower EBP scores. The level of EBP use by French community pharmacists needs to be improved to ensure that good-quality, science-based advice is given to customers.